Design and Development of Semi-Direct Copra Dryer for Flat Terrain - Lesidan, Mencius B. (International Coconut Community Journal, 2020)
The study was conducted to design and develop a semi-direct dryer for flat terrain. This dryer was designed to provide farmers an alternative to traditional and existing dryers particularly the semi-direct and indirect dryers. The components of the dryer were drying bed, plenum chamber, tunnel and firing chamber. It has a capacity of 2,000 nuts and the husks from the nuts were used as fuel for the dryer. The means of the average drying temperature on the front, middle and rear portions of the drying platform were 56.5 oC, 58.2 oC, and 58.4 oC, respectively. The average time of drying in bringing down the moisture content of the copra from 50% to 12% wet basis was 24 hours using only 66.30% of the husks. As of January 2017, the total cost of the dryer with shed was P 61,100.00 and the computed break-even cost was P 1.82/kg. The performance of the dryer is comparable to the existing dryers.